Hubungan Program Jampersal dengan Cakupan K4 pada Ibu Hamil - Bekti Yuniyanti; Tuti Sukini; Pramono Giri Kriswoyo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The aim of this study was to analyze the correlation between Jampersal program with K4 scope among pregnant women in Mungkid Primary Health Care, Magelang. The study was analytic survey using cross sectional approach. The population was 66 women in their third semester pregnancy during August 2013. The result of the study shows that there is correlation between Jampersal program with K4 scope of pregnant women in working area of Mungkid Primary Health Care. We suggest the local mother and child unit in Mungkid Primary Health Care to increase the socialization about Jampersal program to the pregnant women.